Numerical investigation of wave induced thrust on a submerged hydrofoil - Xing, Jingru; Stagonas, Dimitris; Hart, Phil; Zhang, Chengchun; Yang, Jianhui; Yang, Liang (American Institute of Physics (AIP), 2024)
Submerged flapping hydrofoils have the capability to directly convert wave energy into thrust, offering a sustainable approach to marine propulsion. This research employs computational fluid dynamics (CFD) to analyze the propulsion mechanism of wave-induced flapping hydrofoils. Initially validated through established benchmarks and experimental results with foil in uniform flow, the CFD model was then applied to examine the generation of thrust by flapping hydrofoils in heading regular wave. The study reveals a distinct transition from drag to thrust, characterized by the patterns of vortex flow. For the first time, the influence of pitch stiffness on this propulsion process is extensively explored, identifying optimal wave conditions and pitch stiffness for the application of future eco-friendly marine systems.
Keywords: 4015 Maritime Engineering; 40 Engineering; 4008 Electrical engineering; 4012 Fluid mechanics and thermal engineering